2021
DOI: 10.3390/sym13040610
|View full text |Cite
|
Sign up to set email alerts
|

Trade Volume Prediction Based on a Three-Stage Model When Arctic Sea Routes Open

Abstract: With the advancement of global warming, the Arctic sea routes (ASRs) may open for the entire year. The ASRs will be far more competitive than they are now, and they will be the major international sea routes in the future. To date, most studies have researched the economic feasibility in the short term from a company’s perspective. To help to plan the shipping market in the future, we developed a three-stage model to simulate the trade demand of the ASRs for the long term. This model firstly considers the seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…They found that a relative majority of these papers came to the conclusion that Arctic transit is profitable, but also that there is a very significant diversity of methods, parameters, and assumptions. Recently published simulations may still be very enthusiastic about the potential for Arctic transit, like Manta, 32 Sun et al, 33 Sui et al, 34 or several Chinese-led studies about Arctic shipping. 35 However, the picture is now more nuanced with several papers underlining the fact that despite sea ice melt, Arctic transit remains a challenging market from the operational and marketing points of view, with a limited profitability.…”
Section: Models and Simulations Keep Depicting Profitable Arctic Ship...mentioning
confidence: 99%
“…They found that a relative majority of these papers came to the conclusion that Arctic transit is profitable, but also that there is a very significant diversity of methods, parameters, and assumptions. Recently published simulations may still be very enthusiastic about the potential for Arctic transit, like Manta, 32 Sun et al, 33 Sui et al, 34 or several Chinese-led studies about Arctic shipping. 35 However, the picture is now more nuanced with several papers underlining the fact that despite sea ice melt, Arctic transit remains a challenging market from the operational and marketing points of view, with a limited profitability.…”
Section: Models and Simulations Keep Depicting Profitable Arctic Ship...mentioning
confidence: 99%